A study - V.M. Abbasov; Hany M. Abd El-Lateef; L.I. Aliyeva; E.E. Qasimov; I.T. Ismayilov; Mai M. Khalaf (Egyptian Journal of Petroleum)
The influence of the concentration of novel surfactants based on corn oil on the corrosion behavior of carbon steel in CO2 saturated solution at different temperatures was studied. The investigation involved weight loss, LPR corrosion rate and extrapolation of cathodic and anodic Tafel lines method. Results obtained show that the surfactants studied are efficient corrosion inhibitors for carbon steel in CO2 saturated brine. The inhibition efficiency (IE%) increases with an increase in the concentration of the studied surfactant. The inhibition process was attributed to the formation of the adsorbed film on the metal surface that protects the surface against the corrosive agent. The data exhibited that the inhibition efficiency slightly increases with increasing temperature. The surface activity of the synthesized surfactant solutions was determined using surface tension measurements at 25 °C. Adsorption of inhibitors was found to obey the Langmuir isotherm. The standard enthalpy, ΔHads.°, entropy, ΔSads.° and free energy changes of adsorption were evaluated; the calculated values of ΔHads.° and ΔGads° were negative while those for ΔSads.° were positive. Mainly, all the above results are suggestive of chemisorption of the surfactant molecules on the metal surface. Scanning electron microscopy (SEM) and Energy dispersive X-ray fluorescence (EDRF) observations of the electrode surface confirmed the existence of such an adsorbed film.